(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Defect detection in Malay House can be demeanoured by using two types of methods which is through visual inspection and via Priority Ranking System. To judge the building condition, it is good to have a thorough evaluation, so that a reliable recommendation can be made within a short period of time. This evaluation being carried out using the visual inspection on site and Prioritize Ranking System. The simple methodology of the system is using the numerical coding for the survey checklist. For the data under the priority ranking system then can be used as to foresee the condition of the house; either dilapidated, fair, or good. Furthermore, the system enables the surveyor to identify the major types of defects and the location of defects occurred. Through this, the surveyor can list out the element to be repaired in order of priority. The system is tested to the small-scale timber traditional house namely Rumah Melayu near the School of Housing, Building, and Planning (HBP).Â